(untitled) (International Journal of Food and Nutritional Sciences, 2022)
All nations and all people share the same planet our mother earth. Since industrial revolution took place, gradually modernization resulted in the fast growth of the economies leading to exploitation of natural resources and polluting the environment from production and consumption of hazardous products by both producers and consumers. There is a growing interest among the consumers all over the world regarding protection of environment. The Covid-19 pandemic is far more than a health crisis, it has unpredictably changed consumers whole way of life. Consumers priorities have become centered on the most necessary needs include food hygiene, sanitary products, pharmacy products etc. Green marketing imparts a proactive strategy for the companies to cater the market by imparting nature friendly products and services, simultaneously the focus is on continuous innovations in creating green technologies, green products and development of new marketing strategies to meet consumer needs and wants. Hence this is a conceptual paper examines the green technologies and its impact on environment that influence business firms to adopt green marketing for sustainable development of green products.